Clinical wisdom and interventions in acute and critical care : a thinking-in-action approach - Benner, Patricia E. (Springer Pub., 2011)
"[This book is] a lavishly detailed guide to the essence of becoming an expert nurse ... I believe this book will secure a place on most educators' and expert clinicians' bookshelves. Every once in a while a better book comes along; this is one of those times." Joan E. Lynaugh, PhD, RN, FAAN. Professor Emeritus, University of Pennsylvania School of Nursing. (From the Foreword). A classic research-based text in nursing practice and education, this newly revised second edition explains, provides first-hand accounts of the hard-earned experiential wisdom of expert nurses.